Medically important arboviruses of the United States and Canada. - Calisher, C H (1994)
Of more than 500 arboviruses recognized worldwide, 5 were first isolated in Canada and 58 were first isolated in the United States. Six of these viruses are human pathogens: western equine encephalitis (WEE) and eastern equine encephalitis (EEE) viruses (family Togaviridae, genus Alphavirus), St. Louis encephalitis (SLE) and Powassan (POW) viruses (Flaviviridae, Flavivirus), LaCrosse (LAC) virus (Bunyaviridae, Bunyavirus), and Colorado tick fever (CTF) virus (Reoviridae, Coltivirus). Their scientific histories, geographic distributions, virology, epidemiology, vectors, vertebrate hosts, transmission, pathogenesis, clinical and differential diagnoses, control, treatment, and laboratory diagnosis are reviewed. In addition, mention is made of the Venezuelan equine encephalitis (VEE) complex viruses (family Togaviridae, genus Alphavirus), which periodically cause human and equine disease in North America. WEE, EEE, and SLE viruses are transmitted by mosquitoes between birds; POW and CTF viruses, between wild mammals by ticks; LAC virus, between small mammals by mosquitoes; and VEE viruses, between small or large mammals by mosquitoes. Human infections are tangential to the natural cycle. Such infections range from rare to focal but are relatively frequent where they occur. Epidemics of WEE, EEE, VEE, and SLE viruses have been recorded at periodic intervals, but prevalence of infections with LAC and CTF viruses typically are constant, related to the degree of exposure to infected vectors. Infections with POW virus appear to be rare. Adequate diagnostic tools are available, but treatment is mainly supportive, and greater efforts at educating the public and the medical community are suggested if infections are to be prevented.